Effects of a Short Strategy Training on Metacognitive Monitoring across the Life-span - von der Linden, Nicole; Löffler, Elisabeth; Schneider, Wolfgang (Frontline Learning Research, 2016)
The present study was conducted to explore the potential positive influence of a short strategy training on metacognitive monitoring competencies covering a life-span approach. Participants of four age groups (3rd-grade children, adolescents, younger and older adults) concluded a paired-associate learning task. Additionally, they gave delayed Judgments-of-Learning (JOLs), that is, they rated their certainty that they would later be able to recall specific details correctly, and Confidence Judgements (CJs), that is, they rated their certainty that the provided answers in the recall test were correct. Half of the participants underwent a short strategy training in order to enhance their recollection of contextual details thus providing a diagnostic basis for forming metacognitive judgements. Results revealed significant gains in memory performance after completing the strategy training. Moreover, a positive effect of the strategy training on JOLs and CJs differentiation and accuracy could be detected. Effects were most pronounced for children and older adults. Participants who had completed the strategy training also reported a decrease of familiarity-based metacognitive judgments and were able to identify memories for which no reliable cues existed more easily than participants in the control condition. Accordingly, improvements in monitoring performance seemed to be due to a shift in underlying cues. In sum, this study integrates traditional aims from the relatively separately existing lines of metacognitive research in the developmental and cognitive literature and adds to understanding and improving monitoring judgments in a life-time sample.